(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: Recent clinical studies suggest that oxidative stress is one of the key players in the pathogenesis of coronavirus disease 2019 (COVID-19), and N-acetylcysteine (NAC), a potent antioxidant, has been shown to improve clinical outcomes in COVID-19 patients. We conducted a systematic review and meta-analysis of the literature published on the therapeutic intervention of NAC on COVID-19 infection. Methods: We searched PubMed, Google Scholar, and Science Direct. We identified and screened eight studies with 20,503 participants, including 2,852 in the NAC-treated group and 17,651 in the placebo group, which reported the effect of NAC on COVID-19 infection. A meta-analysis was performed using forest plots under fixed effect estimates based on the standardized mean difference (SMD) and risk ratio (RR). Results: Pooled analysis showed that NAC was associated with lower mortality in patients with COVID-19 compared with the placebo group [RR, 0.65; (95% CI: 0.56 to 0.75); p < 0.0001]. Similarly, C-reactive protein (CRP) [SMD, −0.32; (95% CI: −56 to −0.09); p = 0.0070] and D-dimer [SMD, −0.35, (95% CI: −0.59 to −0.10; p = 0.0062] levels were significantly decreased, and the oxygenation marker, PaO2 /FiO2 ratio, was increased in the NAC-treated group compared with the placebo group [SMD, 0.76; (95% CI: 0.48 to 1.03); p < 0.0001]. Conclusion: Although the number of included studies was minimal, this meta-analysis suggests that NAC may have a positive effect on COVID-19 outcomes, specifically, a significant decrease in CRP and D-dimer levels and a significant increase in oxygen saturation, which decreased mortality. We have also presented a comprehensive review of the role and mechanisms of NAC in patients with COVID-19. J. Adv. Vet. Anim. Res., 10(2): 157–168, June 2023 http://doi.org/10.5455/javar.2023.j665